(untitled) (Revista Electrónica REDINE, 2018)
This work presents of investigation had as purpose develop didactic activities based on the use of the Canaima as educational tool for the optimization of the significant learning in the students of the second degree section "B", of Basic School Bolivariana "Gladys Celina Lobo of Carnevalli", located in the Liberating municipality, of the condition Merida. The study there rests on an investigation action participant designed in five phases: I diagnose, Planning, Execution, Evaluation and Systematizing. The key informants were constituted by twenty-five (25) students and (1) teacher. For the compilation of the information they used as technology the observation; since instruments there was in use a comprising list of check of seven (7) indicators to observing and with a scale of response of two alternatives It Is Observed and Is not Observed, besides the record of the diary of the investigator. As for the validity and reliability of the instruments there was applied the method of the triangulation in which there was demonstrated that a correspondence exists between the information thrown by the key informants. The diagnosis threw, that the docents do not motivate to the students to use the portable Canaima, it applies few strategies for the education, which affects unfavorably in that the TIC’S do not join, with the intention of strengthening the significant learnings in the students. For this reason, they were planned, executed and evaluated didactic strategies using the Canaima for the strengthening of the education and the significant improvement of the learning of the involved students.